1987
DOI: 10.1021/bi00375a043
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein cross-linking in calcium-enriched human erythrocytes and activated platelets

Abstract: Treatment of human erythrocytes with Ca2+, in the presence of ionophore A23187, causes the formation of high molecular weight (greater than 10(6)) membrane protein polymers. This phenomenon, known to involve cross-linking of essentially all of the band 4.1 and 2.1 (ankyrin) proteins, as well as some spectrin, band 3, and hemoglobin molecules, could be prevented by preincubating the cells with a noncompetitive inhibitor of intrinsic transglutaminase, 2-[3-(diallylamino)propionyl]benzothiophene, at concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…This suggested that the releasable pool of EPA was not "metabolically exhausted." Alternatively, ionophore could have acted on erythrocytes (17,18), as well as platelets, thereby initiating eicosanoid metabolism in this cellcell interaction via different mechanisms than collagen or thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the releasable pool of EPA was not "metabolically exhausted." Alternatively, ionophore could have acted on erythrocytes (17,18), as well as platelets, thereby initiating eicosanoid metabolism in this cellcell interaction via different mechanisms than collagen or thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…TG2-mediated cross-linking can be uncoupled from proteolysis by differential inhibitors (165), or by a few days of blood bank storage, which greatly diminishes Ca 2ϩ -induced proteolysis without impairing TG2-catalyzed modification of membrane skeleton (171).…”
Section: Tg2 and Erythrocytesmentioning
confidence: 99%
“…Several members of this family have been characterized (Phillips et al, 1990;Kim et al, 1991;Aeschlimann et al, 1998;Grenard et al, 2001) (Table II). These include Factor XIIIa, which is involved in stabilization of fibrin clots and in wound healing (Siefring Jr et al, 1978;Lorand and Graham, 2003), TGase 4, which is involved in the cross-linking of seminal fluid (Dubbink et al, 1998), Band 4.2, an inactive TGase, which is a structural protein in erythroblasts and erythrocytes (Lorand et al, 1987), TGase 2, a ubiquitously expressed TGase with multiple functions (Fesus and Piacentini, 2002;Griffin et al, 2002), and the epidermal-specific TGase, TGase 1 (Phillips et al, 1990;Polakowska et al, 1991), TGase 3 (Kim et al, 1994a), and TGase 5 (Candi et al, 2001(Candi et al, , 2002(Candi et al, , 2004Grenard et al, 2001). Four TGase family members are expressed in keratinocytes and/or in epidermal tissues-TGase 1, TGase 2, TGase 3, and TGase 5 (Table III).…”
Section: Tgase In Keratinocytesmentioning
confidence: 99%